Catalogue of the Ctenostylidae (Diptera, Schizophora) of the World - Pereira-Colavite, A.; Mello, R. L. (Zootaxa, 2014)
A catalogue of Ctenostylidae of the world is presented comprising 14 described species in seven recognized genera. An unnamed species of Ctenostylum Macquart from Costa Rica is also listed. All valid and invalid names and synonyms are presented, totaling 33 names. All references known to us from the taxonomic and biological literature, including references for figures and plates are included. Condition and sex of the type material, type location and geographic distributions with new records for some species are also included. Lochmostylia lopesi Keiser and Tauroscypson andina Aczél have their distributional records enlarged to Paraná (Brazil) and Rondônia (Brazil) respectively. Tauroscypson andina is recorded from Brazil for the first time.